A Study on Decentralized Planning and Development in Villages India: Exploring the Role of Decentralized Planning in Village Development in India (Journal of Advances and Scholarly Researches in Allied Education, 2018)
In this paper, idea of decentralized planning is talked about in detail alongside the short history of decentralized planning in India since freedom. Decentralized planning which is related with community Participation is likewise talked about for the models given by the diverse research over the time. The idea of development set forth by various individuals is additionally talked about in detail. The examples of overcoming adversity as village development through community improvement and community participation are talked about to close the part.